2021
DOI: 10.1186/s12909-021-02559-1
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms about the COVID-19 pandemic: knowledge, attitudes and practices from medical students

Abstract: Background As the disease caused by the novel coronavirus has spread globally, there has been significant economic instability in the healthcare systems. This reality was especially accentuated in Ecuador where, the shortage of healthcare workers combined with cultural and macroeconomic factors has led Ecuador to face the most aggressive outbreak in Latin America. In this context, the participation of final-year medical students on the front line is indispensable. Appropriate training on COVID-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 23 publications
(16 reference statements)
6
22
0
1
Order By: Relevance
“…Earlier works, using similar surveys, have reported higher rates among Ecuadorian (80.4%), Malaysian (80.5%) and Chinese (90%) citizens [20,23,24]. Similar results have been observed among Colombians (76.8%) and Ecuadorian medical students (≥70.0%) [27,36]. Therefore, the level of knowledge reported here cannot be considered sufficient, which demonstrates that there is plenty of work to be done if COVID-19 literacy is expected to increase in the country.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Earlier works, using similar surveys, have reported higher rates among Ecuadorian (80.4%), Malaysian (80.5%) and Chinese (90%) citizens [20,23,24]. Similar results have been observed among Colombians (76.8%) and Ecuadorian medical students (≥70.0%) [27,36]. Therefore, the level of knowledge reported here cannot be considered sufficient, which demonstrates that there is plenty of work to be done if COVID-19 literacy is expected to increase in the country.…”
Section: Discussionsupporting
confidence: 77%
“…In general, research assessing the knowledge of COVID-19 among university students has revealed that information regarding symptoms, infection and prevention strategies are well understood. However, such studies did not include questions about the origin of the virus, its characteristics and the efficacy of unproven treatments [27,38,[45][46][47]. The current report shows that these subjects are not entirely understood by undergraduate students and so must be included in further investigations.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Healthcare workforce shortages have resulted in healthcare students being strongly encouraged to volunteer (10). Several studies have found students to be highly motivated to volunteer in medical-related work (12), such as being community volunteers (15), ventilator therapy assistants, and nursing assistants (16,17) as this may provide an opportunity for them to continue their education efficiently by returning to clinical rotations. Moreover, healthcare students have taken up roles in educating the public and increasing their awareness of the COVID-19 pandemic (18).…”
Section: Introductionmentioning
confidence: 99%